2016
DOI: 10.1016/j.eja.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Climate, soil and land-use based land suitability evaluation for oil palm production in Ghana

Abstract: a b s t r a c tIn the past decade, oil palm (Elaeis guineensis Jacq.) has become the world's most important oil crop. The large demand for palm oil has resulted in a rapid expansion of oil palm cultivation across the globe. Because of the dwindling availability of land in Southeast Asia, most expansion of the industry is expected in Central and South America and sub-Saharan Africa, where land with suitable agro-ecological conditions is available. Using Ghana as a case study, a method for evaluating areas that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 27 publications
0
59
1
8
Order By: Relevance
“…Hujan umumnya terjadi pada sore dan malam hari, hal ini sangat menguntungkan untuk budidaya kelapa sawit. Hasil perhitungan menunjukkan bahwa lokasi penelitian mengalami defisit air pada tahun 2014-2017 berturut-turut sebesar 214 mm, 251 mm, 63 mm, dan 0 mm, yang berarti masih sesuai (favourable) untuk pengembangan tanaman kelapa sawit (Rhebergen et al, 2016).…”
Section: Pan (Panen)unclassified
“…Hujan umumnya terjadi pada sore dan malam hari, hal ini sangat menguntungkan untuk budidaya kelapa sawit. Hasil perhitungan menunjukkan bahwa lokasi penelitian mengalami defisit air pada tahun 2014-2017 berturut-turut sebesar 214 mm, 251 mm, 63 mm, dan 0 mm, yang berarti masih sesuai (favourable) untuk pengembangan tanaman kelapa sawit (Rhebergen et al, 2016).…”
Section: Pan (Panen)unclassified
“…Evaluasi kesesuaian lahan menggunakan metode matching yaitu mencocokkan antara persyaratan ekologis tanaman (agro-ecological requirement) masoyi terhadap karakteristik tiap unit lahan yang meliputi kondisi tanah, iklim, dan topografi (Kawy & El-Magd, 2012;Rhebergen, Fairhurst, Zingore, Fisher, Oberthür, & Whitbread, 2016).…”
Section: Evaluasi Kesesuian Lahanunclassified
“…Sustainable production projects should also sensitize small-scale plantations to desist from encroaching on river banks and swampy areas to cultivate oil palm. A study by Rhebergen et al (2016) also found opportunities for large-scale oil palm plantation development is limited, however, and recommended smallholder production or yield intensification on land already planted as a feasible strategy for oil palm expansion in Ghana. This could also reduce the requirement for further land clearance for new plantations to meet the growing demand for palm oil.…”
Section: Environmental Issues Plantationsmentioning
confidence: 99%
“…The high demand for palm oil and it products have resulted in a rapid expansion of oil palm cultivation across the world. Due to the lack of land availability in Southeast Asia, large expansion of the oil palm industry is expected in sub-Saharan Africa, particularly in West-Africa where land with suitable agroecological conditions is available (Rhebergen et al, 2016). The oil palm industry in Ghana has developed over the last two decades into an important industry in the agricultural sector of the economy (Kabutey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%